A ECONOMIA POLÍTICA DA TRANSFORMAÇÃO DO NORDESTE: de Furtado a Unger - Sávio Teixeira, Carlos (Caderno CRH, 2014)
<!DOCTYPE html PUBLIC "-//W3C//DTD HTML 4.01 Transitional//EN"> 70 Teixeira Este artigo analisa duas propostas dereorganizaçãoestrutural da sociedade nordestina, elaboradas em momentos distintos,uma sob a liderança intelectual de Celso Furtado e a outradeMangabeira Unger. Argumenta que ambas partem da premissa de que oenfrentamento dos graves problemas da região mais desigualdopaís requer ousada reconstruçãoinstitucional,assim como a adoção de políticaspúblicasque objetivem enfrentar os constrangimentos estruturais daregião e não apenas amenizá-los.Sustenta que aproposta que deu origem à SUDENE, capitaneada por Furtado,serviu de inspiração para a segunda empreitadamaisrecente, sendo as duas iniciativas baseadas em ideias que ultrapassamuma perspectiva meramente redistributivista. PALAVRAS-CHAVE: Nordeste. Mudança estrutural.Reconstrução institucional. Celso Furtado.MangabeiraUnger. THEPOLITICAL ECONOMY OF THETRANSFORMATION OF THE NORTHEAST: from Furtado to Unger Carlos Sávio Teixeira This paper analyzes two proposals of structural reorganization ofnortheastern society, prepared at different moments in time, one underCelso Furtado’s intellectual leadership and the other underMangabeira Unger’s leadership. It argues that both stem fromthepremise that the fight against the serious problems faced by thecountry’s most unequal region requires bold institutionalreconstruction, as well as the adoption of public policies that confront the structural constraints of theregion, rather than just lessen them. It reinforces the idea that theproject that gave origin to SUDENE (Superintendence for the Developmentof the Northeast), headed by Furtado, served as inspiration to thesecond latest venture, since the two initiatives were based on ideasthat surpass a merely redistributivist perspective. KEY WORDS: Northeast, structural change, institutional reconstruction,Celso Furtado, Mangabeira Unger. L’ÉCONOMIEPOLITIQUE DELA TRANSFORMATION DU NORD-EST: de Furtado à Unger Carlos Sávio Teixeira Cet article analyse deux propositions de réorganisationstructurelle de la société du nordestélaborées à des momentsdifférents,l’une sous le leadership intellectuel de Celso Furtado etl’autre de Mangabeira Unger. On y argumente que toutes deuxpartent de la prémisse selon laquelle les affrontement desgraves problèmes de la région la plusinégalitairedu pays suppose une reconstruction institutionnelle courageuse ainsi que l’adoption de politiques publiques prêtesàaffronter les contraintes structurelles de la région et nonpasseulement les atténuer. On y affirme que la proposition quiadonné naissance à la SUDENE, menée parFurtado, aservi d’inspiration à une deuxièmeentreprise plusrécente, ces deux initiatives étantfondées surdes idées allant audelà d’uneperspective purementdistributive. MOTS-CLÉS: Nord-est, changement structurel, reconstructioninstitutionnelle, Celso Furtado, Mangabeira Unger. <small style="color: rgb(0, 0, 0); font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: rgb(255, 255, 255);">PublicaçãoOnlinedo Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: rgb(0, 0, 0); font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: rgb(255, 255, 255); display: inline ! important; float: none;"> <small style="color: rgb(0, 0, 0); font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: rgb(255, 255, 255);">PublicaçãoOnlinedo Caderno CRH: http://www.cadernocrh.ufba.br